Analisis Pengaruh Harga Dan Kualitas Produk Terhadap Minat Beli Konsumen Sepeda Motor Listrik Di Depok - Hidayat, Agung Rahmat; Siska, Elmira (Jurnal Mahasiswa Kreatif, 2024)
. Rapid technological innovation is impacting various aspects of life, including the transportation sector. One example is the shift from conventional motorcycles using fossil fuels to electric motorcycles, which are more environmentally friendly and efficient. In Indonesia, particularly in Depok, there is a growing trend in the use of electric motorcycles, supported by government policies and public awareness of environmental issues. This study aims to analyze the influence of price and product quality on consumer purchasing intentions for electric motorcycles in Depok. The approach used is a quantitative method, with primary and secondary data collected through observation, questionnaires, interviews, literature reviews, and documentation. Data were analyzed using SPSS, including data quality tests, classical assumptions, t-tests, F-tests. The results show that price partially has a positive and significant effect on consumer purchase intention (t-value 4.469 > t-table 1.9991 and sig. value 0.00 < 0.05). Product quality also partially has a positive and significant effect on consumer purchase intention for electric motorcycles in Depok (t-value 2.918 > t-table 1.9991 and sig. value 0.000 < 0.05). The implication of these findings is that affordable pricing and good product quality can increase consumer interest in electric motorcycles in Depok.